2020
DOI: 10.1021/acsaem.0c01407
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electrochemical CO2 Reduction Activity via Charge Transfer and sp-Band Filling in a Au Thin Layer on Ag

Abstract: Producing practical chemical feedstocks via electrochemical CO 2 reduction is a promising technology for carbon recycling and renewable energy storage. To improve CO 2 reduction performance, electrocatalysts with high activity and selectivity must be developed. In this study, Au layers of varying thicknesses were sputtered on polycrystalline Ag catalysts to promote the selective reduction of CO 2 to CO. The results show that a 2 nm Au layer sputtered on polycrystalline Ag exhibited a faradaic efficiency of 83.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…[36,37] Accordingly, the electron density of Bi as compared to that of Au 0 . [38,39] The Bi 4f 7/2 and Bi 4f 5/2 peaks assigned to Bi 3+ shift to higher binding energy from 158.1 and 163.4 eV to 158.5 and 163.8 eV. [40] Such red shift (about 0.4 eV) of Bi 4f peaks indicates the close connection for electron transfer from Bi 2 O 3 to Au again, which is in agreement with the Raman spectra (Figure 1c).…”
Section: Resultssupporting
confidence: 78%
“…[36,37] Accordingly, the electron density of Bi as compared to that of Au 0 . [38,39] The Bi 4f 7/2 and Bi 4f 5/2 peaks assigned to Bi 3+ shift to higher binding energy from 158.1 and 163.4 eV to 158.5 and 163.8 eV. [40] Such red shift (about 0.4 eV) of Bi 4f peaks indicates the close connection for electron transfer from Bi 2 O 3 to Au again, which is in agreement with the Raman spectra (Figure 1c).…”
Section: Resultssupporting
confidence: 78%
“…the CO FE of Au20Ag10 reached to 89.01% at −0.9 V, which was much higher than that of Au20Ag05 (60.58%), Au20 (58.14%), Au20Ag50 (39.69%), Au20Ag100 (36.04%), and Ag100 (34.09%). According the FE order of Au20Ag10 > Au20Ag05 > Au20 > Au20Ag50 > Au20Ag100 > Ag100, a proper ratio between Au and Ag in these bimetallic catalysts had synergistic effects [ 24 ] and promoted the selective CO 2 to CO. Results showed that, with the increase of Ag content, the bimetallic catalytic performance was enhanced first due to the enlarged coupling and synergistic effects between Au and Ag.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported previously that the synergistic effect in bimetallic catalysts could improve the CO 2 RR performance. [ 24 ] Therefore, X‐ray photoelectron spectroscopy (XPS) was performed to confirm the chemical compositions and electronic interactions in the catalysts. Figure shows the high‐resolution Au 4f spectra of the six catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation